Pengaruh Idiosinkratik Nurdin Abdullah Terhadap Keberhasilan Kerjasama Indonesia-Jepang di Kabupaten Bantaeng - Muhammad Fadhil (Journal of International and Local Studies, 2020)
Leader’s characteristic’s or idiosyncratic personality becomes one of the factor of what or which policy will they implement in their region. One leader in Indonesia which has a significant affect in Indonesia’s political system is a non-state actor, Nurdin Abdullah. Nurdin Abdullah has a significant idiosyncratic affect towards the success of cooperation happening between Indonesia and Japan in South Sulawesi. Cooperation happening in South Sulawesi between Indonesia and Japan started in the regency of Bantaeng. In this academic writing, writer will explain about the idiosyncratic aspects of Nurdin Abdullah that strongly affects the success of cooperation between Indonesia and Japan happening in the regency of Bantaeng. Through analytical descriptive research method, the results shows that in his time studying for his Master’s and Doctor’s Degree in Japan, he adapted Japanese values that influenced his ardour and policy to cooperate with Japan thus making his policy centered on cooperating with Japan.